ANALYZING THE VALUES AND EFFECTS OF POWERPOINT PRESENTATIONS - Hadiyanti, K.M. Widi; Widya, Widya (LLT Journal: A Journal on Language and Language Teaching, 2018)
PowerPoint Presentation (PPtP) is now quite common in many aspects of life, not only at schools (Yilmazel-Sahin, 2007). It facilitates events in various ways owing to its practicality (Craig & Armenic, 2006). In classes, it provides advantages for both students and teachers, but it may be problematic as well (Davies et al., 2009; Oommen; Taylor, 2012). Therefore, Howard & Conway (1985) recommended verifying if studentsâ viewpoints may maximize its contribution for class empowerment. This study focused on how students appreciated the values of PPP and how it affected lecturers. It involved 90 students responding to a questionnaire asking their standpoint about the use of PPP including commentary and suggestion. Results revealed that in general, participants out looked positively towards PPP and its impact to teachers. It aided students and teacher in the learning-teaching process, although it was occasionally blamed as not engaging or even boring.DOI: doi.org/10.24071/llt.2018.Suppl2108